2012
DOI: 10.1161/circresaha.111.261388
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Atherosclerosis

Abstract: Atherosclerosis is classed as a disease of aging, such that increasing age is an independent risk factor for the development of atherosclerosis. Atherosclerosis is also associated with premature biological aging, as atherosclerotic plaques show evidence of cellular senescence characterized by reduced cell proliferation, irreversible growth arrest and apoptosis, elevated DNA damage, epigenetic modifications, and telomere shortening and dysfunction. Not only is cellular senescence associated with atherosclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
323
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 720 publications
(372 citation statements)
references
References 189 publications
(196 reference statements)
8
323
2
3
Order By: Relevance
“…The cotreatment of cells with either NAC or caffeine inhibited the effects of L5 on DDR pathway activation. TP53 stabilization is critical for relaying the DDR and for executing the senescence response (Wang & Bennett, 2012; Zhan et al., 2010). We found that the small interfering RNA‐mediated silencing of TP53 in HAECs efficiently blocked the L5‐induced increase in SA‐β‐Gal staining and cellular senescence (Figure 5c–e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cotreatment of cells with either NAC or caffeine inhibited the effects of L5 on DDR pathway activation. TP53 stabilization is critical for relaying the DDR and for executing the senescence response (Wang & Bennett, 2012; Zhan et al., 2010). We found that the small interfering RNA‐mediated silencing of TP53 in HAECs efficiently blocked the L5‐induced increase in SA‐β‐Gal staining and cellular senescence (Figure 5c–e).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, traditional cardiovascular risk factors have been shown to induce premature cardiovascular senescence (Erusalimsky, 2009). In vascular cells, the senescence response is believed to promote atherogenesis via the release of pro‐inflammatory cytokines and decreased nitric oxide production (Wang & Bennett, 2012). In preclinical models, the genetic or pharmacologic blockade of the senescence response has been shown to slow the progression of atherosclerosis (Mercer, Gray, Figg, Kumar, & Bennett, 2012; Zhan, Suzuki, Aizawa, Miyagawa, & Nagai, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Aging is associated with endothelial cell dysfunction, and endothelial cell dysfunction is thought to be critical for the development of various vascular diseases (Wang & Bennett, 2012). However, the entire picture of age‐related endothelial dysfunction still remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Aging of endothelial cells (ECs) alters their structure and/or function, and is a critical event resulting in deterioration of vascular integrity (Tian & Li, 2014). Indeed, vascular aging is an independent risk factor of cardiovascular diseases that impair vascular health (Lakatta & Levy, 2003) and is now recognized as a target for intervention to achieve a healthier old age (Wang & Bennett, 2012). For that reason, understanding of the significance of age‐associated changes in the vascular endothelium is essential for the development of a therapeutic strategy to maintain vascular integrity (Brunner et al ., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggests senescent cell burden can be dramatically increased by chronological aging or in models of progeria (Lecka‐Czernik et al ., 1997; Baker et al ., 2004; Varela et al ., 2005), high‐fat feeding (Shi et al ., 2007), diabetes (Verzola et al ., 2008), tobacco exposure (Nyunoya et al ., 2006), or atherosclerosis (Wang & Bennett, 2012), and short‐term treatment with ‘senolytic’ drugs in chronologically aged or progeroid mice alleviates several aging‐related phenotypes (Zhu et al ., 2015a,b). However, effects of long‐term senescent cell clearance on vascular reactivity and structure with aging or chronic hypercholesterolemia remain unknown.…”
Section: Introductionmentioning
confidence: 99%